The Other Side of Abyssal Psychoanalysis - Robert Beshara (EJP import test, 2021)
Summary: This essay offers a critique of Freudo-Lacanian psychoanalysis, which is read not only as a modern field but also as a colonial project. The attempt is not to reject psychoanalysis altogether, for it contains within itself the potential for its own liberation. Rather, the aim of the critique is expanding psychoanalysis beyond its comfort zone within modern epistemology by way of the decolonial theorizing of Boaventura de Sousa Santos.
Keywords: decoloniality; Lacan; Psychoanalysis; Santos